2014
DOI: 10.2337/db14-1282
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Induces Interleukin-1β–Mediated Islet Inflammation and β-Cell Dysfunction Independently of Vasoconstrictive Effects

Abstract: Pathological activation of the renin-angiotensin system (RAS) is associated with the metabolic syndrome, and the new onset of type 2 diabetes can be delayed by RAS inhibition. In animal models of type 2 diabetes, inhibition of the RAS improves insulin secretion. However, the direct effects of angiotensin II on islet function and underlying mechanisms independent of changes in blood pressure remain unclear. Here we show that exposure of human and mouse islets to angiotensin II induces interleukin (IL)-1-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 54 publications
(59 reference statements)
1
55
0
Order By: Relevance
“…The high abundance of IL-1R1 on β-cells is likely the reason for higher sensitivity of β-cells to IL-1 action as compared to other islet cells [17], [18]. The contributing factors to islet inflammation and increased IL-1β levels in T2D are still not completely understood, but it appears that multiple factors such as elevated glucose, fatty acids, angiotensin II, and amyloid formation may contribute to this process [11], [12], [13], [14], [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…The high abundance of IL-1R1 on β-cells is likely the reason for higher sensitivity of β-cells to IL-1 action as compared to other islet cells [17], [18]. The contributing factors to islet inflammation and increased IL-1β levels in T2D are still not completely understood, but it appears that multiple factors such as elevated glucose, fatty acids, angiotensin II, and amyloid formation may contribute to this process [11], [12], [13], [14], [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear if this improved glycemic control is a result of the normalization of vasoconstriction in tissues (e.g., muscle and pancreas) or due to the local inhibition of RAS. Sauter et al (17) show that chronic treatment with angiotensin II in high fat-fed mice that also received the vasodilator hydralazine (to prevent hypertension) caused impaired glucose-stimulated insulin secretion and deteriorated glucose tolerance that was not due to the changes in insulin sensitivity, supporting the direct effects of angiotensin II on b-cell function. Interestingly, neutralizing IL-1b signaling reduced angiotensin II-mediated islet inflammation, restored glucose-stimulated insulin secretion, and improved glucose homeostasis.…”
mentioning
confidence: 99%
“…In this issue of Diabetes, Sauter et al (17) report another interesting mechanism that contributes to islet inflammation and local IL-1b production in patients with T2D. Using in vitro islet studies and a mouse model of T2D, the authors show that the renin-angiotensin system (RAS), a major system in blood pressure regulation, contributes to islet inflammation and b-cell dysfunction independent of its effects on glucose homeostasis mediated via vasoconstriction.…”
mentioning
confidence: 99%
“…In a recent study, it was reported that a 4 week chronic infusion of angiotensin II impaired glucose tolerance in vivo and abolished glucose stimulated insulin secretion independent of changes in blood pressure (86). Angiotensin II also had deleterious effects on pancreatic islet mitochondrial function and insulin secretion due to IL-1β and NF-κB mediated inflammation in islets (86).…”
Section: Relevance To Shock Trauma and Critical Illnessmentioning
confidence: 99%
“…Angiotensin II also had deleterious effects on pancreatic islet mitochondrial function and insulin secretion due to IL-1β and NF-κB mediated inflammation in islets (86). Since components of the RAS, including angiotensin-converting enzyme 2 (ACE2), are found in rodent and human pancreatic islets (8789), and overexpression of ACE2 in pancreas of diabetic mice improve glycemic control (89), the efficacy of RAS blockade to ameliorate insulin resistance in burn injury may also be due to improvements in pancreatic islet function.…”
Section: Relevance To Shock Trauma and Critical Illnessmentioning
confidence: 99%